Data‐Centric Approach: A Novel Systematic Approach for Cyber Physical System Heterogeneity in Smart Grid. Issue 5 (28th January 2019) - Jia, Kunqi; Wang, Zhihua; Fan, Shuai; Zhai, Shaopeng; He, Guangyu
Abstract : As a typical cyber physical system (CPS), a smart grid should facilitate more robust integration and interoperability of information models and subsystems so that the performance of the physical system can be optimized. However, the intrinsic complexity and heterogeneity of CPS are two of the biggest obstacles to interoperation and interconnection among various information models and subsystems. In order to address the dilemma, this paper proposed a systematic, data‐centric system design approach comprehensively including data‐oriented system architecture, data resources abstraction and data‐driven mechanisms. To be specific, the autonomous decentralized system (ADS) theory is introduced to establish the data‐centric system architecture. A MQTT/MQTT‐SN‐based communication protocol, which supports not only IP‐based devices but also non‐IP devices, is proposed to meet the requirement of publish–subscribe mechanism of the ADS‐based system architecture. A data‐centric meta‐interface is proposed to formalize the data resources abstraction. A Lebesgue sampling‐based data exchange mechanism, which is proven tractable but effective, is proposed to realize the data‐driven mechanism. As user energy management system (UEMS) is an integral part of smart grid, a realistic UEMS for heating project is considered a typical case to study the performance of the proposed data‐centric system. This paper is one of the first few papers that systematically propose a systematic data‐centric system design approach for a smart grid, which is supported by aspects of system architecture, communication protocol and data exchange mechanism. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.